Study of Cool Jets and Evolution of Kelvin-helmholtz Instability in the Solar Atmosphere - Singh, Balveer (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Study of Cool Jets; Evolution of Kelvin-helmholtz; Instability in the Solar Atmosphere